Diagnostic Approach to Pediatric Autoimmune Neuropsychiatric Disorders Associated With Streptococcal Infections (PANDAS): A Narrative Review of Literature Data - Prato, Adriana; Gulisano, Mariangela; Scerbo, Miriam; Barone, Rita; Vicario, Carmelo M.; Rizzo, Renata (Frontiers in Pediatrics, 2021)
Paediatric autoimmune neuropsychiatric disorders associated with streptococcal infections (PANDAS) are clinical conditions characterized by the sudden onset of obsessive‑compulsive disorder and/or tics, often accompanied by other behavioural symptoms in a group of children with streptococcal infection. PANDAS-related disorders including Paediatric acute-onset neuropsychiatric Syndrome (PANS), Childhood Acute Neuropsychiatric Symptoms (CANS) and Paediatric Infection Triggered Autoimmune Neuropsychiatric Disorders (PITANDs), have been also described. Since first defined in 1998, PANDAS has been considered a controversial diagnosis. A comprehensive review of the literature was performed on PubMed and Scopus databases, searching for diagnostic criteria and diagnostic procedures of PANDAS and related disorders. We propose a test panel to support clinicians in the work-out of PANDAS/PANS patients establishing an appropriate treatment. However, further studies are needed to improve our knowledge on these acute-onset neuropsychiatric conditions.